Analysis of the motivational model of Edgar Schein’s eight anchors and the motivational model used by a company in the fnancial sector in the city of Cartagena - Cuadrado-Álvarez, Rosario; Pineda-Portacio, Luis Miguel; Castellanos-Oviedo, Yeferson; Santana-Díaz, Leydis (EFIM Ediciones, 2020)
Motivation at work has been the object of study throughout history, given that she provides the required stimuli to a person to connect with the position and the organization. The motivational plan of an organization must respond to the real needs of the people who make it up, for this reason, the advantages of the theory of the Eight Anchors applicable in the organization are conceptualized and identifed.